Can fashion be sustainable? Trajectories of change in organizational, products and processes, and socio-cultural contexts - Paola Bertola; Chiara Colombi (Sustainability: Science, Practice, & Policy)
This article conducts an in-depth exploration of the current landscape of fashion sustainability, providing a comprehensive framework that contextualizes the subsequent contributions that comprise this Special Issue. By delineating three pivotal dimensions of action, we set the stage for a nuanced examination that reviews the realms of organizational change, innovation within fashion products and processes, and the tangled interplay of socio-cultural transformations. These dimensions collectively lay the foundation for a holistic analysis of how the fashion industry navigates the complexities of sustainability, encompassing shifts in management paradigms, advancements in design and production, and cultural factors that underpin the sustainable fashion discourse. Through an extensive analysis, the article not only presents a panoramic view of the current state of the art regarding fashion and sustainability but also constructs a robust conceptual framework that serves as a guiding compass for navigating the subsequent sections within this Special Issue. This framework is designed to encapsulate the multiple facets of sustainability within the fashion domain, acting as a roadmap to discern and understand the evolving landscape. This lens invites readers to journey beyond the surface, delving into the perspectives that define the transition toward a more sustainable fashion future.